Members’ experiences of a neuromuscular disorder online support group - Meade, Oonagh (2013)
Introduction: Neuromuscular disorders (NMDs) cause wasting and weakening of muscles. People affected by NMDs and their carers can experience a number of adverse psychosocial consequences, which can be exacerbated by the rare nature of many of these disorders. This makes access to medical information, timely diagnoses, supportive care and peer support difficult. Options for receiving peer support are increasing through the development of online support groups (OSGs) for people affected by NMDs.